Peran Lingkungan Masyarakat Terhadap Kearifan Lokal dalam Perspektif Manajemen Pendidikan Islam - Raihana Aulia Sukhairani; Ihwa Rismi; Muhammad Izham (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In this modern era, competition in education is increasing and various strategies are carried out to attract the attention of the public or interested parties, in this case external stakeholders, so that they have high enthusiasm for the world of education, especially educational institutions. To attract the attention of the community, the institution always tries to establish good cooperative relations with various parties, including the community. In this study, the authors used library research, namely research carried out using literature in the form of books, journals, notes and reports on research results and the results of previous studies. In order to involve the participation of these community members in the development of education in schools/universities, it is appropriate for education managers through community leaders to actively arouse their attention. Managers can invite these figures to discuss forms of cooperation in improving education. In this meeting they will share opinions, exchange ideas, to find alternatives to improve education. Based on the results and discussion above, it can be concluded that the relationship between school and community cooperation is very important. In the field of educational institution cooperation relations, the task that must be carried out in the field of public relations is to provide an explanation of school policies, situations, and school developments. Accommodate community suggestions and opinions to advance the school.